Penelitian Sastra Pemaknaan Heuristik, Hermeneutik, dan Kritik Sosial dalam Kumpulan Puisi Pahlawan dan Tikus Karya A. Mustofa Bisri: Kajian Semiotika - Hasmiyatni, Dwi Meilani; Herlina, Lina; Anwar, Rivaldi (CV. Eduartpia Publisher, 2024)
This research examines the meaning of heuristics, hermeneutics and social criticism in the book A Collection of Poems on Heroes and Mouse by A. Mustofa Bisri, using a qualitative descriptive method with Michael Riffaterre's semiotic approach. The research data comes from heuristic and hermeneutic analysis of six poems in this book, namely